Intestinal Flora Disruption and Novel Biomarkers Associated With Nasopharyngeal Carcinoma - Jiang, Haiye; Li, Jian; Zhang, Bin; Huang, Rong; Zhang, Junhua; Chen, Ziwei; Shang, Xueling; Li, Xisheng; Nie, Xinmin (Frontiers in Oncology, 2019)
Background: Nasopharyngeal carcinoma (NPC) is a malignant nasopharyngeal disease with a complicated etiology that occurs mostly in southern China. Intestinal flora imbalance is believed to be associated with a variety of organ malignancies. Current studies revealed that the destruction of intestinal flora is associated with NPC, and many studies have shown that intestinal flora can be used as a biomarker for many cancers and to predict cancer. Methods: To compare the differences in intestinal flora compositions and biological functions among 8 patients with familial NPC (NPC_F), 24 patients with sporadic NPC (NPC_S), and 27 healthy controls (NOR), we compared the intestinal flora DNA sequencing and hematological testing results between every two groups using bioinformatic methods. Results: Compared to the NOR group, the intestinal flora structures of the patients in the NPC_F and NPC_S groups showed significant changes. In NPC_F, Clostridium ramosum, Citrobacter spp., Veillonella spp., and Prevotella spp. were significantly increased, and Akkermansia muciniphila and Roseburia spp. were significantly reduced. In NPC_S, C. ramosum, Veillonella parvula, Veillonella dispar, and Klebsiella spp. were significantly increased, and Bifidobacterium adolescentis was significantly reduced. A beta diversity analysis showed significant difference compared NPC_F with NOR based on Bray Curtis (P = 0.012) and Unweighted UniFrac (P = 0.0045) index, respectively. The areas under the ROC curves plotted were all 1. Additionally, the concentrations of 5-hydroxytryptamine (5-HT) in NPC_F and NPC_S were significantly higher than those of NOR. C. ramosum was positively correlated with 5-HT (rcm: 0.85, P < 0.001). A functional analysis of the intestinal flora showed that NPC_F was associated with Neurodegenerative Diseases (P = 0.023) and that NPC_S was associated with Neurodegenerative Diseases (P = 0.045) as well. Conclusion: We found that NPC was associated with structural imbalances in the intestinal flora, with C. ramosum that promoted the elevation of 5-HT and opportunistic pathogens being significantly increased, while probiotics significantly decreased. C. ramosum can be used as a novel biomarker and disease prediction models should be established for NPC. The new biomarkers and disease prediction models may be used for disease risk prediction and the screening of high-risk populations, as well as for the early noninvasive diagnosis of NPC.